2019
DOI: 10.31744/einstein_journal/2019ao4905
|View full text |Cite
|
Sign up to set email alerts
|

Posterior quadratus lumborum block for primary total hip arthroplasty analgesia: a comparative study

Abstract: Objective To compare analgesia and opioid consumption for patients undergoing primary total hip arthroplasty with preoperative posterior quadratus lumborum block with patients who did not receive quadratus lumborum block.Methods The medical records of patients undergoing unilateral total hip arthroplasty between January 1st, 2017 and March 31, 2018 were reviewed, and 238 patients were included in the study. The primary outcome was postoperative opioid consumption in the first 24 postoperative hours. Secondary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 15 publications
3
22
0
Order By: Relevance
“…Morphine consumption was chosen as the primary outcome, consistent with other studies on pain relief in total hip arthroplasty. [4][5][6]13,16 Secondary outcomes included intraoperative sufentanil consumption; morphine consumption in the postanesthesia care unit; area of cutaneous sensory loss sensation; pain scores at rest at extubation time and 2, 6, 12, and 24 h after extubation; pain scores during passive 90° hip flexion at 2, 6, and 24 h after extubation; maximal pain score during the intervals between extubation time and 2 h after extubation and between 2 and 24 h after extubation; motor blockade at 2 and 6 h after extubation; time to first standing and ambulation; hospital length of stay; and adverse events including block-related side effects. The sample size has been estimated a priori with calculation based on the anticipated opioid consumption difference between study groups.…”
Section: Sample Size Estimation and Statistical Analysismentioning
confidence: 99%
“…Morphine consumption was chosen as the primary outcome, consistent with other studies on pain relief in total hip arthroplasty. [4][5][6]13,16 Secondary outcomes included intraoperative sufentanil consumption; morphine consumption in the postanesthesia care unit; area of cutaneous sensory loss sensation; pain scores at rest at extubation time and 2, 6, 12, and 24 h after extubation; pain scores during passive 90° hip flexion at 2, 6, and 24 h after extubation; maximal pain score during the intervals between extubation time and 2 h after extubation and between 2 and 24 h after extubation; motor blockade at 2 and 6 h after extubation; time to first standing and ambulation; hospital length of stay; and adverse events including block-related side effects. The sample size has been estimated a priori with calculation based on the anticipated opioid consumption difference between study groups.…”
Section: Sample Size Estimation and Statistical Analysismentioning
confidence: 99%
“…A recent comparative study showed that hospital length of stay following total hip arthroplasty was found to be significantly decreased in patients receiving QL block compared with no block. 7 Kukreja et al 8,19 found in 2 separate studies that both the anterior and posterior QL block are effective at decreasing opioid requirements following hip arthroplasty in the first 48 hours postoperatively. A case report of the QL block used for 2 cases of femoral neck fracture and revision hip arthroplasty found it provided significant pain control without hip flexor or quadriceps weakness.…”
Section: Discussionmentioning
confidence: 99%
“…[ 28 ] They also revealed that the post-operative opioid requirement and the post-operative pain score were significantly decreased in patients undergoing primary total hip replacement under general or spinal anaesthesia if they received preoperative posterior QLB. [ 29 ] Furthermore, Green et al . evaluated the use of transmuscular QLB in patients undergoing hip surgeries.…”
Section: Discussionmentioning
confidence: 99%